Composite material, application product thereof and manufacturing method of composite material

By attaching silicon-containing polymers to the surface of the metal-organic structure to form a composite material, the problem of reduced chemical stability of MOF on the wiring board is solved, and higher chemical stability and signal transmission performance are achieved.

CN119343409AInactive Publication Date: 2025-01-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046152.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-15
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, metal organic structures (MOFs) are susceptible to the influence of alkali liquid and etching liquid during installation of electronic components on the wiring board, resulting in a decrease in the chemical stability of the insulating layer, which in turn affects signal transmission and mechanical strength.

Method used

A composite material containing a metal-organic structure and a silicon-containing polymer containing polymers with a backbone selected from styrene, butadiene, ethylene, cyclic olefins and fluorine-containing olefin units is used, and the silicon-containing polymer is polymerized by bonding substances are attached to the surface of the MOF to improve chemical stability.

Benefits of technology

Significantly improves the chemical stability of materials containing metal-organic structures and reduces sensitivity to alkali and etching solutions, thereby improving signal transmission and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343409A_ABST
    Figure CN119343409A_ABST
Patent Text Reader

Abstract

A composite material according to one aspect of the present disclosure is provided with a metal-organic structure and a silicon-containing polymer. The silicon-containing polymer includes a main chain including at least one selected from the group consisting of a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit, and a fluorine-containing olefin unit. The silicon-containing polymer includes, for example, a functional group represented by-SiR3-n (OX) n, n is an integer of 1 to 3, X represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, a moiety bonded to a metal organic structure, or a moiety bonded to a silicon atom other than the silicon atom of the functional group, at least one of the X is a moiety bonded to a metal organic structure, and R represents a hydrocarbon group having 1 to 10 carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a composite material, an application product thereof and a method for manufacturing the composite material. Background Art

[0002] Patent Document 1 describes a resin composition for forming an insulating film containing a metal organic structure and a curable resin. Patent Document 2 describes an organosilicon compound for use in a rubber composition. Non-Patent Documents 1, 2, and 3 disclose methods for chemically modifying the surface of a metal organic structure.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-80327

[0006] Patent Document 2: Japanese Patent Application Publication No. 2016-191040

[0007] Non-patent literature

[0008] Non-patent literature 1: Shuliang Yang, Li Peng, Daniel T. Sun, Mehrdad Asgari, Emad Oveisi, Olga Trukhina, Safak Bulut, Abbas Jamalia and Wendy L. Queen, Chem. Sci., 2019, Vol. 10, 4542-4549

[0009] Non-patent literature 2: Sanfeng He, Hongliang Wang, Cuizheng Zhang, Songwei Zhang, Yi Yu, Yongjin Lee and Tao Li, Chem. Sci., 2019, Vol. 10, 1816-1822

[0010] Non-patent document 3: Yuxiu Sun, Qi Sun, Hongliang Huang, Briana Aguila, Zheng Niu, Jason A. Perman and Shengqian Ma, J. Mater. Chem., 2017, Vol. 5, 18770-18776

[0011] Non-patent document 4: Jonathan P. Ruffley, Isabella Goodenough, Tian-Yi Luo, Melissandre Richard, Eric Borguet, Nathaniel L. Rosi and J. Karl Johnson, J. Phys. Chem., 2019, Vol. 123, 19748-19758

[0012] Non-patent literature 5: Anoopa Thomas, Rafiq Ahamed and Muthuramalingam Prakash, RSC Adv., 2020, Vol. 10, 39160-39170

[0013] Non-Patent Literature 6: Fangyuan Tian, ​​Andrew M. Cerro, Amber M. Mosier, Hannah K. Wayment-Steele, Ryan S. Shine, Aileen Park, Elizabeth R. Webster, Lewis E. Johnson, Malkiat S. Johal and Lauren Benz, J. Phys. Chem., 2014, Vol. 118, 14449-14456

[0014] Non-patent document 7: Dong Yang, Melike Babucci, William H. Casey and Bruce C. Gates, ACS. Cent. Sci., 2020, Vol. 6, 1523-1533

[0015] Non-Patent Literature 8: Gurpreet Kaur, Sigurd Oien-Odegaard, Andrea Lazzarini, Sachin Maruti Chavan, Silvia Bordiga, Karl Petter Lillerud and Unni Olsbye, Cryst. Growth. Des., 2019, Vol. 19, 4246-4251 Summary of the invention

[0016] Problems to be solved by the invention

[0017] The present disclosure aims to improve the chemical stability of materials comprising metal-organic structures.

[0018] Means for solving problems

[0019] The composite material disclosed in the present invention comprises: a metal organic structure and a silicon-containing polymer.

[0020] The silicon-containing polymer includes a main chain including at least one selected from a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit, and a fluorine-containing olefin unit.

[0021] Effects of the Invention

[0022] According to the present disclosure, the chemical stability of a material including a metal organic structure can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a diagram showing a schematic structure of a composite material in Embodiment 1.

[0024] Figure 2 This is a flowchart showing an example of a method for producing a composite material in the first embodiment.

[0025] Figure 3 This is a diagram showing a schematic structure of a resin composition in the third embodiment.

[0026] Figure 4 This is a cross-sectional view of the film with resin in the fifth embodiment.

[0027] Figure 5 This is a cross-sectional view of the metal foil with resin in the sixth embodiment.

[0028] Figure 6 It is a cross-sectional view of a metal-clad laminate in the seventh embodiment.

[0029] Figure 7 This is a cross-sectional view of a wiring board in the eighth embodiment.

[0030] Figure 8 It is a graph showing the infrared absorption spectrum of the composite material of Example 1 and the infrared absorption spectrum of ZIF-8.

[0031] Fig. 9 3 is a diagram showing the O1s XPS spectrum of the composite material of Example 1.

[0032] Fig.10 : is a graph showing the O1s XPS spectrum of ZIF-8.

[0033] Fig.11 Graphs showing the X-ray diffraction pattern of the particles synthesized in Example 2 and the X-ray diffraction simulation pattern of UiO-67. DETAILED DESCRIPTION

[0034] (Insights that form the basis of this disclosure)

[0035] In recent years, the application of the fifth-generation mobile communication system (5G) in the field of electronics has expanded, and the performance level required of electronic devices has increased. For example, in order to make the communication speed faster than previous generations, 5G uses a higher frequency band. Therefore, electronic components that support high frequencies are required in electronic devices.

[0036] The transmission loss in the transmission path depends on the frequency. The higher the signal frequency, the greater the transmission loss. In addition, the transmission loss depends on the relative dielectric constant and dielectric loss tangent of the insulating layer. Therefore, in order to reduce the transmission loss of high-frequency signals, the materials including the substrate material and the sealing material constituting the insulating layer are required to have low relative dielectric constant and low dielectric loss tangent.

[0037] In addition, with regard to large-capacity communications such as 5G, due to the use of high-frequency bands, the transmission distance of radio waves is short. Therefore, it is necessary to increase the output power of electronic equipment. In addition, with the realization of high integration and miniaturization, the installation density of circuits is also improved. If you want to meet these necessities, the heat generation per unit area of ​​the wiring board increases. Therefore, the wiring board is required to have high heat dissipation. In order to improve the heat dissipation of the wiring board, a filler (filler) with excellent thermal conductivity is contained in the substrate material constituting the insulating layer of the wiring board, thereby improving the thermal conductivity of the wiring board.

[0038] In recent years, metal organic framework (MOF) has attracted attention as a filler for insulating layers. MOF is an insulating material also known as porous coordination polymer (PCP) or nanoporous metal complex. MOF is a crystalline porous material composed of metal ions or metal clusters and cross-linking ligands. MOF is a material with a particularly low relative dielectric constant. MOF has a low relative dielectric constant at a level required in antenna substrates for communication base stations, for example, in a high frequency band of GHz to THz, it can meet a relative dielectric constant of less than 2.0. In addition, with respect to MOF, the dielectric loss tangent can also be reduced by appropriate selection of the crystal structure. Therefore, MOF has attracted attention as a filler for the insulating layer of wiring boards for various communication purposes. For example, a resin composition for forming an insulating film containing MOF and a curable resin is described in Patent Document 1. As a filler for the insulating layer, MOF has a negative thermal expansion coefficient like conventional inorganic fillers such as silica particles. In addition, MOF has a larger porosity than other porous materials, and therefore has a lower relative dielectric constant. Furthermore, in the case of MOF, the dielectric loss tangent can be reduced by appropriately selecting the crystal structure.

[0039] However, in the process of installing electronic components on the wiring board, the wiring board is exposed to alkali solution and etching solution. If the material of the insulating layer is deteriorated by exposure to these liquids, the relative dielectric constant and dielectric loss tangent of the insulating layer will change. In the wiring board, the change of the relative dielectric constant and dielectric loss tangent during the installation process may cause the deterioration of transmission loss, the generation of signal noise caused by the inconsistency of impedance matching, and other unfavorable situations. In addition, the deterioration of the material of the insulating layer causes the reduction of the mechanical strength of the insulating layer, the volatilization of the generated by-products, etc., resulting in the dimensional change of the wiring board. In addition, the molded product containing the sealing material should not be deteriorated under high temperature and high humidity. Therefore, for the filler of the insulating layer, resistance to liquid and water vapor, that is, chemical stability, is required. The so-called chemical stability, specifically, is alkali resistance, acid resistance and moisture resistance.

[0040] However, since MOF has a three-dimensional porous structure constructed by self-aggregation of metal ions or metal clusters and cross-linking ligands, the structure is easily deteriorated by alkali or acid. If the structure of MOF deteriorates and the voids disappear, the chemical stability decreases. The reduction in chemical stability is particularly significant in MOFs with a structure with a large void ratio.

[0041] In order to improve the chemical stability of MOF, a method for chemically modifying the surface of MOF is proposed. For example, in non-patent document 1, it is recorded that by polymerizing dopamine molecules on the surface of MOF, a dense polydopamine layer is formed on the surface of MOF, and then the fluoroalkylthiol molecules are bonded to the polydopamine layer by Michael addition reaction. Thus, in non-patent document 1, it is recorded that the acid resistance and alkali resistance of MOF are improved. In addition, in non-patent document 2, it is recorded that by coating the surface of MOF with a polyacrylate polymer having a polymerization initiation point, and then polymerizing it in the presence of the polyacrylate polymer, various double-layer polymers are formed on the surface of MOF. Thus, in non-patent document 2, it is recorded that the acid resistance and alkali resistance of MOF are improved.

[0042] But, polydopamine and polyacrylate polymer are owing to having a large amount of polar functional groups, therefore with regard to the chemical modification method of recording in non-patent literature 1 and non-patent literature 2, it is possible to cause the rising of relative dielectric constant and dielectric loss tangent.In addition, with regard to the chemical modification method of recording in non-patent literature 1 and non-patent literature 2, monomer component or oligomer component easily invade the space interior of MOF during polyreaction.If polyreaction is carried out in the space interior of MOF, then the space is blocked, and relative dielectric constant and dielectric loss tangent rise.Monomer component or oligomer component are particularly remarkable in the MOF with the large structure of void ratio to the invasion of space interior.

[0043] A method for chemically modifying the surface of MOF at the molecular level has also been proposed. For example, in non-patent document 3, it is recorded that by reacting a molecule having a phosphoric acid site at the end of an alkyl chain with MOF, the metal site on the surface of MOF is bonded to the phosphoric acid site of the alkyl chain, thereby coating the outer surface of MOF with an alkyl chain. Thus, in non-patent document 3, it is recorded that MOF obtains high water repellency while maintaining porosity. In addition, it is recorded that high resistance to acidic aqueous solutions and alkaline aqueous solutions is also obtained. However, according to the research of the present inventors, it has been determined that the chemical stability is insufficient with respect to the chemical modification method described in non-patent document 3.

[0044] Among them, an organosilicon compound having a specific structure is disclosed in Patent Document 2. Patent Document 2 states that when the organosilicon compound is added to a rubber composition, the hysteresis loss of the cured product is greatly reduced. However, Patent Document 2 does not state or teach that the surface of the filler is modified with the organosilicon compound to thereby improve the chemical stability of the filler.

[0045] The present inventors have conducted intensive research on improving the chemical stability of materials including metal organic structures (MOFs), and as a result, have come up with the composite material disclosed herein.

[0046] (Overview of one aspect of the present disclosure)

[0047] The composite material involved in the first embodiment of the present disclosure comprises: a metal organic structure and a silicon-containing polymer. The silicon-containing polymer comprises the following main chain, and the main chain comprises at least one selected from styrene units, butadiene units, ethylene units, cycloolefin units and fluorine-containing olefin units. According to the above structure, the chemical stability of the material containing the metal organic structure can be improved.

[0048] In the second aspect of the present disclosure, for example, according to the composite material of the first aspect, the silicon-containing polymer may be attached to the surface of the metal-organic structure. According to the above configuration, the chemical stability of the material including the metal-organic structure can be further improved.

[0049] In a third aspect of the present disclosure, for example, in the composite material according to the first or second aspect, the metal organic structure may include metal oxide clusters. According to the above configuration, the chemical stability of the material including the metal organic structure can be improved.

[0050] In a fourth aspect of the present disclosure, for example, in the composite material according to any one of the first to third aspects, the metal oxide cluster may include a Zr oxide cluster. According to the above configuration, the chemical stability of the material including the metal organic structure can be improved.

[0051] In the fifth embodiment of the present disclosure, for example, according to the composite material involved in any one of the first to fourth embodiments, the silicon-containing polymer may include a first side chain containing a silicon atom and an oxygen atom, and may be bonded to the metal organic structure via the silicon atom and the oxygen atom. According to the above configuration, the chemical stability of the material containing the metal organic structure can be further improved. In addition, without damaging the chemical stability of the material containing the metal organic structure, it is also possible to make the material containing the metal organic structure and other compounds composite.

[0052] In the sixth aspect of the present disclosure, for example, according to the composite material involved in any one of the first to fifth aspects, the silicon-containing polymer may include -SiR 3-n (OX) n wherein n is an integer from 1 to 3, and X represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, a portion bonded to the metal organic structure, or a portion bonded to a silicon atom other than a silicon atom of the functional group. At least one of X is a portion bonded to the metal organic structure. R represents a hydrocarbon group having 1 to 10 carbon atoms. According to the above configuration, the chemical stability of the material containing the metal organic structure is further improved.

[0053] In the seventh aspect of the present disclosure, for example, according to the composite material involved in any one of the first to sixth aspects, the silicon-containing polymer may include the following second side chain, wherein the second side chain includes at least one selected from a carbon-carbon double bond and a carbon-carbon triple bond. According to the above configuration, when the composite material is used as a filler, the heat dissipation of the filler is improved.

[0054] In an eighth aspect of the present disclosure, for example, according to the composite material of the seventh aspect, the second side chain may be formed only of a chain structure. According to the above configuration, when the composite material is used as a filler, the heat dissipation property of the filler is improved.

[0055] In a ninth aspect of the present disclosure, for example, in the composite material according to any one of the first to eighth aspects, the main chain may include the butadiene unit. According to the above configuration, the chemical stability of the material including the metal organic structure is further improved.

[0056] In the tenth aspect of the present disclosure, for example, in the composite material according to the ninth aspect, the main chain may include a copolymer including the styrene unit and the butadiene unit. According to the above configuration, the chemical stability of the material including the metal organic structure is further improved.

[0057] In an eleventh aspect of the present disclosure, for example, in the composite material according to the sixth aspect, the silicon-containing polymer may be represented by the following formula (1) containing a plurality of repeating units.

[0058] [Chemical formula number 1]

[0059]

[0060] In the above formula (1), a and d represent numbers greater than 0, b and c represent numbers greater than 0, and R 1 To R 5 Each of the above-mentioned repeating units independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom or -CH3, and the order of the multiple repeating units is arbitrary. According to the above-mentioned structure, the chemical stability of the material including the metal organic structure is further improved.

[0061] In the twelfth aspect of the present disclosure, for example, in the composite material according to the eleventh aspect, in the formula (1), 0.15≤c / (b+c+d) may be satisfied. According to the above configuration, the chemical stability of the material including the metal organic structure is further improved.

[0062] In a thirteenth aspect of the present disclosure, for example, in the composite material according to any one of the first to twelfth aspects, the metal organic structure may include UiO-67. According to the above configuration, excellent dielectric properties can be achieved.

[0063] The filler according to the fourteenth aspect of the present disclosure includes the composite material according to any one of the first to thirteenth aspects. According to the above configuration, a filler having improved chemical stability can be provided.

[0064] The resin composition according to the fifteenth aspect of the present disclosure includes the filler according to the fourteenth aspect. According to the fifteenth aspect, a resin composition having a low dielectric loss tangent and excellent heat resistance can be provided.

[0065] A prepreg according to a sixteenth aspect of the present disclosure includes the resin composition according to the fifteenth aspect or a semi-cured product of the resin composition.

[0066] A film with resin according to a seventeenth aspect of the present disclosure comprises a resin layer including the resin composition according to the fifteenth aspect or a semi-cured product of the resin composition, and a support film.

[0067] The metal foil with resin according to the eighteenth aspect of the present disclosure comprises: a resin layer including the resin composition according to the fifteenth aspect or a semi-cured product of the resin composition; and a metal foil.

[0068] A metal-clad laminate according to a nineteenth aspect of the present disclosure comprises an insulating layer including a cured product of the resin composition according to the fifteenth aspect or a cured product of the prepreg according to the sixteenth aspect, and a metal foil.

[0069] A wiring board according to a twentieth aspect of the present disclosure includes an insulating layer formed of a cured product of the resin composition according to the fifteenth aspect or a cured product of the prepreg according to the sixteenth aspect, and wiring.

[0070] According to the sixteenth to twentieth aspects, various application products suitable for high frequencies can be provided.

[0071] The method for manufacturing a composite material according to the twenty-first embodiment of the present disclosure comprises the step of attaching a silicon-containing polymer to a metal-organic structure. The silicon-containing polymer comprises the following main chain, and the main chain comprises at least one selected from a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit, and a fluorine-containing olefin unit. According to the above structure, a material containing a metal-organic structure with improved chemical stability can be manufactured.

[0072] In the twenty-second aspect of the present disclosure, for example, according to the method for producing a composite material according to the twenty-first aspect, the metal-organic structure may include metal oxide clusters. According to the above configuration, the chemical stability of the material including the metal-organic structure is improved.

[0073] In the twenty-third aspect of the present disclosure, for example, according to the method for producing a composite material of the twenty-first or twenty-second aspect, the number average molecular weight of the silicon-containing polymer may be greater than 1200. According to the above configuration, the chemical stability of the material including the metal organic structure is improved.

[0074] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0075] (Implementation Method 1)

[0076] The following uses Figure 1 and Figure 2 , implementation mode 1 is described.

[0077] [Composite Materials]

[0078] Figure 1 1 is a diagram showing a schematic structure of a composite material 10 in Embodiment 1. The composite material 10 includes a metal organic structure 1 (hereinafter referred to as "MOF1") and a silicon-containing polymer 2. The silicon-containing polymer 2 includes silicon atoms. The silicon-containing polymer 2 includes a main chain including at least one selected from a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit, and a fluorine-containing olefin unit.

[0079] The silicon-containing polymer 2 may be attached to the surface of MOF 1. The silicon-containing polymer 2 may cover at least a portion of the surface of MOF 1. The silicon-containing polymer 2 may cover the entire surface of MOF 1 or only a portion of the surface of MOF 1.

[0080] The silicon-containing polymer 2 is a low-polarity polymer. Compared with silicon-containing low-molecular compounds such as alkylsilane, the silicon-containing polymer 2 can inhibit water molecules, acids and bases from reaching MOF1. Acids are, for example, protons or oxonium ions. Bases are, for example, hydroxide ions. Therefore, when the silicon-containing polymer 2 is attached to the surface of MOF1, the composite material 10 has excellent alkali resistance and acid resistance. That is, the composite material 10 has high chemical stability. It should be noted that in the present disclosure, the so-called "silicon-containing low-molecular compound" refers to an organic silicon compound with a molecular weight of less than 1200.

[0081] Silicon-containing polymer 2 is difficult to invade the pores of MOF1. In addition, the main skeleton of the main chain of silicon-containing polymer 2 is a hydrocarbon group, which does not have a large amount of polar functional groups, such as the polydopamine and polyacrylate polymers used in non-patent literature 1 and non-patent literature 2. Therefore, according to composite material 10, the rise of relative dielectric constant and dielectric loss tangent can also be suppressed. In this way, composite material 10 achieves the improvement of chemical stability while suppressing the rise of relative dielectric constant and dielectric loss tangent.

[0082] [Metal-organic framework (MOF)]

[0083] MOF1 may include one selected from a metal oxide cluster and a zeolite-like imidazolate structure (hereinafter referred to as "ZIF").

[0084] MOF1 may include metal oxide clusters. Examples of metal oxide clusters include M6O x (OH) 8-x A metal oxide cluster having a structural unit represented by a composition formula of . M is a tetravalent Group IV element. M is, for example, Zr, Hf or Ce. The saturated coordination number is 12. M may be Zr. That is, the metal oxide cluster may be a Zr oxide cluster. The cross-linking ligands of such metal oxide clusters include, for example, a carboxylate group (-COO) and a hydroxyl group (-OH).

[0085] MOF1 may have Zr oxide clusters and cross-linking ligands containing carboxylate groups. Such zirconium-based MOFs are also called Zr-MOFs. In Zr-MOFs, the Zr oxide clusters contain Zr6O x (OH) 8-x(0≤x≤8) is a structural unit represented by a composition formula. For such Zr oxide clusters, more than 2 and less than 12 cross-linking ligands containing at least 2 or more carboxylate groups can be bonded. The Zr-MOF having the above structure has high chemical stability and high thermal stability due to the strong bonding of Zr(IV)-O, and has a high porosity. Therefore, Zr-MOF is particularly useful. As Zr-MOF, for example, UiO-66, UiO-67, UiO-68, NU-1000, NU-1103, MOF-808, PCN-224, DUT-52, BUT-30, MIL-140, etc. can be listed.

[0086] Zr-MOF may be, for example, UiO-67. UiO-67 is constructed by a Zr oxide cluster comprising a structural unit represented by the composition formula of Zr6O4(OH)4 and 4,4'-biphenyl dicarboxylate as a cross-linking ligand. UiO-67 is represented by the composition formula of Zr6O4(OH)4(bpdc)6. Wherein, bpdc represents 4,4'-biphenyl dicarboxylate. The helium-converted porosity of UiO-67 calculated in the RASPA software package (https: / / iraspa.org / ) is 68% (refer to non-patent document 4), and it is expected to have a low relative dielectric constant and a low dielectric loss tangent.

[0087] As MOF1, Zr-MOF particles can be used. There is no particular limitation on the shape of the Zr-MOF particles. The shape of the Zr-MOF particles may be, for example, scaly, spherical, ellipsoidal, rod-shaped, etc., or may be amorphous. There is no particular limitation on the average particle size of the Zr-MOF particles. The average particle size of the Zr-MOF particles may be, for example, greater than 0.01 μm and less than 100 μm, or greater than 0.05 μm and less than 50 μm. In the present disclosure, the average particle size of the Zr-MOF particles refers to the median diameter. The so-called median diameter refers to the particle size (d50) when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, using a laser diffraction measuring device.

[0088] MOF1 may include ZIF. MOF1 may be ZIF. ZIF is a general term for MOFs having a three-dimensional crystal structure similar to zeolite. ZIF has a central metal ion with regular tetrahedral 4-coordination (tetrahedron: Td) and a cross-linking ligand containing imidazolate, and is constructed by a coordination bond of metal-imidazolate-metal. Examples of the central metal ion include Zn 2+ 、Co 2+ZIF is useful because it has high thermal stability and high porosity. Examples of ZIF include ZIF-4, ZIF-7, ZIF-8, ZIF-12, ZIF-67, ZIF-90, and ZIF-412. ZIF may contain Zn 2+ With a cross-linkable ligand comprising an imidazolate ester.

[0089] ZIF may be, for example, ZIF-8. ZIF-8 is composed of Zn II The composition formula of ZIF-8 is (2-MeIm)2. 2-MeIm represents 2-methyl imidazolate. ZIF-8 has 2-methyl imidazolate as a ligand and Zn 2+ The cross-linked sodalite crystal structure has high thermal and chemical stability. The helium-converted porosity of ZIF-8 calculated in the RASPA software package (https: / / iraspa.org / ) is 48% (see Non-Patent Document 5), and it is expected to have a low relative dielectric constant and a low dielectric loss tangent.

[0090] As MOF1, ZIF particles can be used. There is no particular limitation on the shape of the ZIF particles. The shape of the ZIF particles can be, for example, scaly, spherical, ellipsoidal, rod-shaped, etc., or amorphous. There is no particular limitation on the average particle size of the ZIF particles. The average particle size of the ZIF particles can be, for example, greater than 0.01 μm and less than 100 μm, or greater than 0.05 μm and less than 50 μm. In the present disclosure, the average particle size of the ZIF particles refers to the median diameter.

[0091] [Silicon-containing polymer]

[0092] The silicon-containing polymer 2 contains silicon atoms. The silicon-containing polymer 2 further contains the following main chain, which contains at least one selected from styrene units, butadiene units, ethylene units, cycloolefin units and fluorine-containing olefin units. Compared with silicon-containing low molecular weight compounds such as alkylsilanes, the silicon-containing polymer 2 can inhibit the access of water molecules, acids and bases. Acids are, for example, protons and oxonium ions. Bases are, for example, hydroxide ions. In addition, due to the structural characteristics of the silicon-containing polymer 2, it is possible to inhibit the adsorption of moisture in the atmosphere. In addition, compared with silicon-containing low molecular weight compounds such as alkylsilanes, the silicon-containing polymer 2 itself is not easily evaporated by heating. Therefore, the silicon-containing polymer 2 is also useful from the perspective of heat resistance.

[0093] In addition to the main chain, the silicon-containing polymer 2 may also include side chains branching from the main chain. The silicon-containing polymer 2 may include multiple side chains. The main chain may include a first main chain composed of mutually bonded carbon atoms. The silicon-containing polymer 2 may include a side chain containing silicon atoms while including the first main chain.

[0094] The silicon-containing polymer 2 may include a first side chain including a silicon atom and an oxygen atom. The silicon-containing polymer 2 may be bonded to MOF1 via the silicon atom and the oxygen atom. More specifically, the silicon-containing polymer 2 may include an oxygen atom bonded to the silicon atom and MOF1.

[0095] The scheme of silicon-containing polymer 2 bonding to MOF1 via silicon atoms and oxygen atoms is envisioned as follows. Usually, inside MOF1, metal ions or metal clusters have a predetermined number of coordinating sites, and cross-linking ligands are bonded to each of these coordinating sites. On the other hand, on the surface of MOF1, at least one site of unbonded cross-linking ligands in the coordinating sites possessed by metal ions or metal clusters remains. The coordinating sites exposed on the surface of MOF1 are Lewis acidic, for example, bonded to Lewis basic oxygen atoms. That is, it is expected that there is a MO bond between the surface of MOF1 and the oxygen atom. M represents a metal atom. Therefore, in the composite material 10, it is expected that at least one MO bond is formed between the silicon-containing polymer 2 and MOF1. In addition, it is known that there is a situation where a hydroxyl group (-OH) is bonded to the remaining coordinating site (for example, refer to non-patent document 6 and non-patent document 7). That is, it is expected that there is an M-OH bond on the surface of MOF1. It is known that the M-OH bond forms a MO-Si bond, for example, through a silane coupling reaction. From the above, it is expected that in the composite material 10, the silicon-containing polymer 2 is bonded to MOF1 by forming at least one MO-Si bond between the silicon-containing polymer 2 and MOF1. In addition, it is also expected that the M-OH bond on the surface of MOF1 forms a hydrogen bond of M-OH-O with the oxygen atom of the silicon-containing polymer. Therefore, it is expected that in the composite material 10, the silicon-containing polymer 2 is bonded to MOF1 by forming at least one M-OH-O bond between the silicon-containing polymer 2 and MOF1.

[0096] For example, when MOF1 is Zr-MOF, it is expected that there are sites or Zr-OH bonds that can coordinate Zr on the surface of MOF 1. Therefore, in this case, it is expected that the silicon-containing polymer 2 is bonded to Zr-MOF by forming at least one Zr-O bond, Zr-O-Si bond, or Zr-OH-O bond between the silicon-containing polymer 2 and Zr-MOF.

[0097] It should be noted that, when Zr-MOF is UiO-67, on the surface of UiO-67, bpdc ligands are bonded to all sites (e.g., 12) that can be coordinated with Zr oxide clusters. Therefore, the sites that can be coordinated with unbonded crosslinking ligands or the sites of Zr-OH bonded with hydroxyl groups are minimal. However, since silicon-containing polymer 2 is bonded to the surface of MOF1, when Zr-MOF is UiO-67, there are also sites or Zr-OH sites that can be coordinated with Zr on the surface of UiO-67, and via these sites, Zr-O bonds, Zr-O-Si bonds, or Zr-OH-O bonds can be formed with silicon-containing polymer 2, so it is believed that silicon-containing polymer 2 can be immobilized on the surface of UiO-67.

[0098] For example, when MOF1 is ZIF-8, it is expected that there are sites or Zn-OH bonds that can coordinate Zn on the surface of ZIF-8. Therefore, in this case, it is expected that the silicon-containing polymer 2 is bonded to ZIF-8 by forming at least one Zn-O bond, Zn-O-Si bond, or Zn-OH-O bond between the silicon-containing polymer 2 and ZIF-8.

[0099] In the composite material 10, if the silicon-containing polymer 2 is fixed on the surface of MOF1 by bonding, it is possible to compound with other compounds without damaging the chemical stability. For example, when you want to obtain a resin composition containing the composite material 10 and other compounds, you need to dissolve it in a prescribed solvent for mixing or a mechanical dispersion treatment process. If the silicon-containing polymer 2 is fixed on MOF1 by bonding, it can be avoided that the silicon-containing polymer 2 does not exist on the surface of MOF1 even in the resin composition obtained after such a process. In the case of forming a resin composition containing MOF1, the silicon-containing polymer 2 and other compounds by a one-stage process, it is also possible to avoid the state in which the silicon-containing polymer 2 does not exist on the surface of MOF1 in the obtained resin composition. In this way, if the silicon-containing polymer 2 is fixed on the surface of MOF1 by bonding, the envisioned chemical stability can also be achieved in the state of the resin composition.

[0100] In addition, in the composite material 10, if the silicon-containing polymer 2 is fixed on the surface of MOF1 by bonding, it can also be expected that the surface of MOF1 is often covered by a low-polar polymer, resulting in an increase in dispersibility in a prescribed solvent. In particular, in a non-polar solvent, the dispersibility is improved. The non-polar solvent is, for example, toluene. Thus, the dispersibility of the composite material 10 in the resin composition is improved, so for example, it can also be expected that the mechanical properties of the resin composition can be improved and the dielectric property fluctuation in the resin composition can be suppressed.

[0101] The silicon-containing polymer 2 may include -SiR3-n (OX) n Represents a functional group. Wherein, n is an integer from 1 to 3, and X represents a hydrogen atom, a hydrocarbon group with a carbon number of 1 to 10, a bonding portion bonded to MOF1, or a bonding portion bonded to a silicon atom other than the silicon atom of the above-mentioned functional group. X as a bonding portion can also be represented by a single bond (-). The hydrocarbon group with a carbon number of 1 to 10 is, for example, an alkyl group with a carbon number of 1 to 10, particularly with a carbon number of 1 to 3. At least one of X is a bonding portion bonded to MOF1. R represents a hydrocarbon group with a carbon number of 1 to 10. The silicon-containing polymer 2 having such a structure is immobilized on the surface of MOF1 via MO-Si bonds. Therefore, the surface of MOF1 is more densely covered with the silicon-containing polymer 2, and thus the chemical stability of the composite material 10 is further improved.

[0102] In by-SiR 3-n (OX) n In the functional group represented by , R may be an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms.

[0103] The alkyl group having 1 to 10 carbon atoms may have any structure of a straight chain, a ring, or a branched structure. Examples of the alkyl group having 1 to 10 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl. Examples of the aryl group having 6 to 10 carbon atoms include phenyl, α-naphthyl, and β-naphthyl.

[0104] The silicon-containing polymer 2 comprises -SiR 3-n (OX) n In the case where X contains a functional group represented by Si-O-Si and X contains a bonding portion bonded to another silicon atom, the silicon-containing polymer 2 contains a siloxane unit represented by Si-O-Si. The silicon-containing polymer 2 may contain a second main chain composed of a siloxane unit. The silicon-containing polymer 2 having such a structure may have a network structure in which the siloxane unit (Si-O-Si) is extended in a mesh shape.

[0105] The silicon-containing polymer 2 may include a second side chain containing at least one selected from a carbon-carbon double bond and a carbon-carbon triple bond. According to such a structure, the carbon-carbon double bond or the carbon-carbon triple bond reacts with the reactive residue of the resin contained in the insulating layer to form a bond, so the adhesion between the composite material 10 and the resin is improved. As a result, the thermal resistance of the interface between the composite material 10 and the resin is reduced, and the thermal conductivity of the insulating layer is improved. And then the heat dissipation of the wiring board is improved. As a group containing a carbon-carbon double bond, for example, vinyl, methallyl, acryloyl, etc. can be listed. The silicon-containing polymer 2 may have one selected from the above, or it may have more than two. From the viewpoint of easy reactivity, the group containing a carbon-carbon double bond is preferably vinyl. As a reactive residue of the resin contained in the insulating layer, vinyl, methallyl, acryloyl, etc. can be listed. As a group containing a carbon-carbon triple bond, for example, ethynyl, propargyl, etc. can be listed. The silicon-containing polymer 2 may have one selected from the above, or it may have more than two. Examples of the reactive residue of the resin contained in the insulating layer include ethynyl and propargyl. At least one selected from a carbon-carbon double bond and a carbon-carbon triple bond may be located at the end of the second side chain. The second side chain may be formed only of a chain structure.

[0106] Note that, from the viewpoint of avoiding degradation due to oxidation, the content ratio of carbon-carbon double bonds and carbon-carbon triple bonds present in the silicon-containing polymer 2 is preferably small.

[0107] The silicon-containing polymer 2 may further include side chains other than the first side chain and the second side chain. The side chains other than the first side chain and the second side chain may have, for example, a cyclic structure. The cyclic structure of the side chain is, for example, an aromatic group.

[0108] The main chain of the silicon-containing polymer 2 may include a butadiene unit. According to the above configuration, the chemical stability of the composite material 10 is further improved.

[0109] The main chain of the silicon-containing polymer 2 may include a copolymer including styrene units and butadiene units. According to the above configuration, the chemical stability of the composite material 10 is further improved.

[0110] The silicon-containing polymer 2 can be represented by the following formula (1) containing a plurality of repeating units. With such a configuration, the chemical stability of the composite material 10 is further improved.

[0111] [Chemical formula number 2]

[0112]

[0113] In the above formula (1), a and d represent numbers greater than 0, b and c represent numbers greater than 0, and R 1 To R 5Each of -SiR is independently a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom or -CH3. However, the order of the plurality of repeating units is arbitrary. 3-n (OX) n The functional groups represented are as described above. In the above formula (1), the bond represented by the wavy line means either the trans form or the cis form or a mixture of both.

[0114] The silicon-containing polymer 2 in the above formula (1) may satisfy 0≤a≤500, 1≤b≤500, 1≤c≤500, 0≤d≤500, or may satisfy 5≤a≤300, 5≤b≤300, 1≤c≤100, 5≤d≤300.

[0115] The silicon-containing polymer 2 in the above formula (1) may satisfy 5≤a≤100, 5≤b≤100, 1≤c≤80, 5≤d≤100, or may satisfy 5≤a≤20, 5≤b≤50, 1≤c≤60, 5≤d≤40.

[0116] In the above formula (1), c represents the number of repetitions of butadiene units having silicon and oxygen in the side chain. (b+c+d) represents the sum of butadiene units having a repetition number b, butadiene units having a repetition number c, and butadiene units having a repetition number d. The silicon-containing polymer 2 in the above formula (1) can satisfy 0.15≤c / (b+c+d). In other words, in the above formula (1), the value calculated using 100×{c / (b+c+d)} can be 15% or more. According to the above composition, the chemical stability of the composite material 10 is further improved. In the above formula (1), the value calculated using 100×{c / (b+c+d)} can be 17% or more. The upper limit of the value calculated using 100×{c / (b+c+d)} is, for example, 80%. However, the value calculated using 100×{c / (b+c+d)} is not particularly limited as long as it is within the range in which desired chemical stability and dielectric properties can be exhibited.

[0117] [Method for producing composite material]

[0118] Next, a method for producing the above-mentioned composite material will be described.

[0119] Figure 2 1 is a flowchart showing an example of a method for producing a composite material 10 in Embodiment 1. The method for producing a composite material 10 includes attaching a silicon-containing polymer 2 to a surface of MOF 1 (step S1). The silicon-containing polymer 2 includes a main chain including at least one selected from a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit, and a fluorine-containing olefin unit.

[0120] In step S1 , the silicon-containing polymer 2 may be bonded to the surface of the MOF 1 via silicon atoms and oxygen atoms.

[0121] MOF1 may include one selected from metal oxide clusters and ZIFs. MOF1 may include metal oxide clusters.

[0122] The silicon-containing polymer 2 represented by the above formula (1) is represented by the following formula (2) before bonding to MOF 1.

[0123] [Chemical formula number 3]

[0124]

[0125] In the above formula (2), R 6 and R 7 Each of them independently represents a hydrocarbon group having a carbon number of 1 to 10. m represents an integer of 1 to 3. a and d represent a number greater than 0, and b and c represent a number greater than 0.

[0126] In the above formula (2), R 6 and R 7 They may independently represent an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms.

[0127] Alkyl groups with 1 to 10 carbon atoms and aryl groups with 6 to 10 carbon atoms, such as -SiR 3-n (OX) n However, in the above formula (2), as the alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 5 carbon atoms is preferred, and an alkyl group having 1 to 3 carbon atoms is more preferred. 6 and R 7 , are independently preferably straight-chain alkyl, more preferably methyl or ethyl.

[0128] In the high frequency band of GHz to THz, the dielectric loss tangent greatly depends on the orientation polarization of the organic molecules contained in the material of the wiring board. Therefore, the hydroxyl groups present on the surface of MOF1 can increase the dielectric loss tangent. However, with respect to the silicon-containing polymer represented by the above formula (2), the silicon-containing polymer acts on the hydroxyl groups present on the surface of MOF1, thereby bonding with the surface of MOF1. The silicon-containing polymer 2 after bonding is represented by the above formula (1). With respect to the composite material 10, the number of hydroxyl groups present on the surface of MOF1 is reduced by the bonding of the silicon-containing polymer 2, so the effect of suppressing the rise of the dielectric loss tangent can also be expected.

[0129] The silicon-containing polymer represented by the above formula (2) can be obtained by the reaction shown in the following scheme. Specifically, a styrene-butadiene copolymer represented by the following formula (3) and an organosilicon compound represented by the following formula (4) are subjected to hydrosilylation in the presence of a catalyst containing a platinum compound, preferably in the presence of a catalyst containing a platinum compound and a co-catalyst. Thus, the silicon-containing polymer represented by the above formula (2) can be obtained.

[0130] [Chemical formula number 4]

[0131]

[0132] The styrene-butadiene copolymer represented by the above formula (3) can be synthesized by using butadiene and styrene as raw monomers, using a known method such as emulsion polymerization or solution polymerization. The styrene-butadiene copolymer represented by the above formula (3) can also be obtained as a commercial product. As commercial products, for example, Ricon 100, Ricon 181, Ricon 184 (the above are made by Cray Valley Co., Ltd.), L-SBR-820, L-SBR-841 (the above are made by Kuraray Co., Ltd.), 1,2-SBS (the above are made by Nippon Soda Co., Ltd.), etc. can be listed.

[0133] Examples of the organosilicon compound represented by the formula (4) include trimethoxysilane, methyldimethoxysilane, dimethylmethoxysilane, triethoxysilane, methyldiethoxysilane, and dimethylethoxysilane.

[0134] It should be noted that the value of c can be maintained before and after the silicon-containing polymer is bonded to the surface of MOF1. That is, the value of c in the above formula (2) is equal to the value of c in the above formula (1). Therefore, in the above formula (2), the silanization rate calculated using 100×{c / (b+c+d)} can be regarded as the silanization rate calculated using 100×{c / (b+c+d)} in the above formula (1).

[0135] In the state before bonding with the surface of MOF1, the number average molecular weight of the silicon-containing polymer can be more than 1200, or more than 5000. According to the above composition, the density coated by the silicon-containing polymer 2 is increased, so the chemical stability of the composite material 10 is improved. There is no particular limitation on the upper limit of the number average molecular weight of the silicon-containing polymer before bonding with the surface of MOF1. The upper limit of the number average molecular weight of the silicon-containing polymer before bonding with the surface of MOF1 is, for example, less than 10000. It should be noted that in the present disclosure, the number average molecular weight is the number average molecular weight calculated using gel permeation chromatography (GPC) for polystyrene conversion.

[0136] In step S1, the silicon-containing polymer 2 can be bonded to the surface of MOF1. For example, when the silicon-containing polymer before bonding to the surface of MOF1 is represented by the above formula (2), the silicon-containing polymer 2 can be bonded to the surface of MOF1 through the following reaction. When the surface of MOF1 is bonded to the silicon-containing polymer 2 via a MO bond or a M-OH-O bond, -SiR 3-n (OX) n The O in is bonded to M or M-OH. When the surface of MOF1 is bonded to the silicon-containing polymer 2 via a MO-Si bond, first, the silicon-containing polymer represented by the above formula (2) is hydrolyzed to generate a silanol group (Si-OH). Then, the silanol group is partially bonded by dehydration condensation with the hydroxyl group present on the surface of MOF1. At this time, a metal-oxygen-silicon bond (MO-Si bond) formed by dehydration condensation is formed between the silicon-containing polymer and the surface of MOF1. As a result, the silicon-containing polymer 2 is fixed to the surface of MOF1 by bonding. Furthermore, dehydration condensation between the silicon-containing polymers 2 can also be promoted by heat treatment or the addition of acid or alkali. As a result, the silicon-containing polymers 2 are continuously bonded to each other via siloxane bonds (Si-O-Si). By operating in this way, the thickness of the layer of the silicon-containing polymer 2 can also be controlled. The thickness of the layer of the silicon-containing polymer 2 can be appropriately selected according to the properties of the MOF 1 , or according to the required dielectric properties and chemical stability, and further according to the properties of the resin of the insulating layer.

[0137] (Implementation Method 2)

[0138] The filler according to the present embodiment includes the composite material 10 according to the first embodiment.

[0139] The filler involved in this embodiment can be a filler for forming an insulating layer. In the present disclosure, the filler for forming an insulating layer is a filler mixed with a resin component as an insulating material for a wiring board or a sealing material in an IC chip. When the filler involved in this embodiment is used as a filler for forming an insulating layer, it is possible to suppress the increase in relative dielectric constant and dielectric loss tangent and improve chemical stability.

[0140] The filler according to the present embodiment can be produced by, for example, kneading the composite material 10 according to the first embodiment and an epoxy resin or a silicone resin, or a non-silicone acrylic resin or a ceramic resin.

[0141] (Implementation 3)

[0142] Figure 3 It is a figure which shows the schematic structure of the resin composition 20 in Embodiment 3. The resin composition 20 contains the filler 22 and the curable resin 24, for example.

[0143] The filler 22 includes the composite material 10 described in Embodiment 1. According to this embodiment, a resin composition 20 having low dielectric loss tangent and excellent heat resistance can be provided. As the filler 22, only the composite material 10 may be used, or other filler materials such as silica particles may be used together with the composite material 10.

[0144] Examples of the curable resin 24 include epoxy resins, cyanate compounds, maleimide compounds, phenolic resins, acrylic resins, polyamide resins, polyamideimide resins, thermosetting polyimide resins, and polyphenylene ether resins. As the curable resin 24, one or a combination of two or more selected from these can be used.

[0145] The resin composition 20 may contain other components. As other components, curing agent, flame retardant, ultraviolet absorber, antioxidant, reaction initiator, silane coupling agent, fluorescent whitening agent, photosensitizer, dye, pigment, tackifier, lubricant, defoamer, dispersant, leveling agent, glossing agent, antistatic agent, polymerization inhibitor, organic solvent, etc. can be listed. As other components, one or a combination of two or more selected from the above can be used as needed.

[0146] (Implementation 4)

[0147] The prepreg according to the fourth embodiment comprises Figure 3 The resin composition 20 or its semi-cured product of the third embodiment shown, and a fibrous substrate. The fibrous substrate is present in the matrix of the resin composition 20 or the semi-cured product. The prepreg is a composite material of the resin composition 20 and the fibrous substrate. According to this embodiment, a prepreg suitable for a wiring board supporting high frequencies can be provided.

[0148] In the present embodiment, semi-cured material refers to a material in which the resin combination 20 is cured to a state midway to a degree that can be further cured. That is, the semi-cured material is a material in a state in which the resin combination 20 is semi-cured. For example, if the resin combination 20 is heated, its viscosity slowly decreases. If heating is continued, curing begins afterwards, and its viscosity slowly rises. In such a case, as a semi-cured state, the state of the resin combination 20 during the time from the moment when the viscosity rises to the moment of complete curing can be listed.

[0149] As the fibrous substrate, known materials used in various laminates for electrical insulating materials can be used. As the fibrous substrate, glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, cotton linter paper, etc. can be listed.

[0150] The resin composition 20 is impregnated into the fibrous base material by treatment such as impregnation or coating. The fibrous base material impregnated with the resin composition 20 is heated under predetermined heating conditions to obtain a prepreg in a pre-cured or semi-cured state according to the present embodiment.

[0151] (Implementation 5)

[0152] Figure 4 : is a cross-sectional view of a film 30 with resin in Embodiment 5. The film 30 with resin includes: a resin layer 32 containing a resin composition 20 or a semi-cured product thereof, and a support film 34. According to this embodiment, a film 30 with resin suitable for an insulating layer can be provided. The resin layer 32 is supported by the support film 34. Figure 4 In the example of FIG. 3 , the support film 34 is disposed on the surface of the resin layer 32. However, another layer such as an adhesive layer may be provided between the resin layer 32 and the support film 34.

[0153] The resin layer 32 includes Figure 3 The resin composition 20 or its semi-cured product of the embodiment 3 shown may contain a fibrous substrate or may not contain a fibrous substrate. As the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used. The resin layer 32 is cured and changed into an insulating layer. An example of such an insulating layer is an insulating layer of a wiring board.

[0154] Any supporting film used for a film with a resin can be used without limitation as the supporting film 34. Examples of the supporting film 34 include resin films such as a polyester film and a polyethylene terephthalate film.

[0155] (Implementation method 6)

[0156] Figure 5 : is a cross-sectional view of a metal foil 40 with resin in Embodiment 6. The metal foil 40 with resin includes: a resin layer 42 containing a resin composition 20 or a semi-cured product thereof, and a metal foil 44. The resin layer 42 is supported by the metal foil 44. According to this embodiment, a metal foil 40 with resin suitable for electronic circuit components such as wiring boards can be provided. Figure 5 In the example of FIG. 4 , the metal foil 44 is disposed on the surface of the resin layer 42. However, another layer such as an adhesive layer may be provided between the resin layer 42 and the metal foil 44.

[0157] The resin layer 42 includes Figure 3 The resin composition or semi-cured product of the embodiment 3 shown may contain a fibrous substrate or may not contain a fibrous substrate. As the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used. The resin layer 42 is cured and changed into an insulating layer. An example of such an insulating layer is an insulating layer of a wiring board.

[0158] As the metal foil 44, metal foil used for a resin-attached metal foil and a metal-clad laminate can be used without limitation. Examples of the metal foil include copper foil and aluminum foil.

[0159] (Implementation 7)

[0160] Figure 6 : is a cross-sectional view of a metal-clad laminate 50 in Embodiment 7. The metal-clad laminate 50 includes an insulating layer 52 and at least one metal foil 54. According to this embodiment, a metal-clad laminate 50 suitable for a wiring board can be provided. The insulating layer 52 includes Figure 3 The cured product of the resin composition 20 of the third embodiment shown or the cured product of the prepreg of the fourth embodiment. The metal foil 54 is arranged on the surface of the insulating layer 52. In this embodiment, the metal foil 54 is arranged on the front surface and the back surface of the insulating layer 52, respectively.

[0161] The metal-clad laminate 50 is typically manufactured using the prepreg of Embodiment 4. For example, 1 to 20 prepregs are stacked to form a laminate. A metal foil is arranged on one or both sides of the prepreg laminate, and heating and pressurizing are performed to obtain the metal-clad laminate 50. Examples of the metal foil 54 include copper foil, aluminum foil, and the like.

[0162] The molding conditions for producing the metal-clad laminate 50 can be applied to the molding conditions for producing, for example, an electrically insulating laminate or a multilayer board.

[0163] (Implementation 8)

[0164] Figure 7 : is a cross-sectional view of a wiring board 60 in Embodiment 8. The wiring board 60 includes an insulating layer 62 and wirings 64. According to this embodiment, a wiring board 60 suitable for high frequencies can be provided. The insulating layer 62 includes Figure 3 The cured product of the resin composition 20 of the third embodiment or the cured product of the prepreg of the fourth embodiment shown in . The wiring 64 is supported by the insulating layer 62. Specifically, the wiring 64 is arranged on the insulating layer 62. The wiring 64 can be formed by partially removing the metal foil.

[0165] By using etching and other methods Figure 6 The metal foil 54 on the surface of the metal-clad laminate 50 shown is patterned (layout), thereby obtaining a wiring board 60 in which wiring 64 forming a circuit is provided on the surface of the insulating layer 62. That is, the wiring board 60 is obtained by partially removing the metal foil 54 on the surface of the metal-clad laminate 50 in a manner to form a circuit.

[0166] A new laminate can be formed by laminating the prepreg of Embodiment 4 on at least one surface of wiring board 60 and heating and pressing the laminate. When the metal foil on the surface of the obtained laminate is patterned to form wiring, a multilayer wiring board is obtained.

[0167] Example

[0168] The present disclosure will be described in detail below by showing examples. The examples are for illustrating the present disclosure and are not intended to limit the present disclosure.

[0169] <<Example 1>>

[0170] [Metal-organic framework (MOF)]

[0171] As MOF, ZIF-8 particles (manufactured by Aldrich, product name: Basolite Z1200) were used.

[0172] [Synthesis of Silicon-Containing Polymers]

[0173] As a silicon-containing polymer, a silicon-containing polymer represented by the above formula (2) was synthesized. Specifically, a styrene-butadiene copolymer represented by the above formula (3) (manufactured by Nippon Soda Co., Ltd., product number: 1,2-SBS) and an organic silicon compound represented by the above formula (4) (manufactured by Tokyo Chemical Industry Co., Ltd., product number: T0135, m=3, R 6 =H) in the presence of a platinum catalyst to carry out hydrosilylation. Thus, the silicon-containing polymer of Example 1 represented by the above formula (2) is obtained. The composition of the obtained silicon-containing polymer is 1 The ratio of the integrated values ​​of the peaks corresponding to the functional groups in the profile obtained by H nuclear magnetic resonance (NMR) measurement (600 MHz) was determined. As the NMR apparatus, JNM ECZ600R manufactured by JEOL was used. As a result, the silicon-containing polymer of Example 1 satisfied the above formula (2) where a=10, b=61, c=13, d=0, m=3, R 6 = methyl (-CH3). The silylation rate of the silicon-containing polymer of Example 1 is 17.6%. It should be noted that the silylation rate is calculated by -SiR 2 3-m (OR 1 ) m The number average molecular weight of the silicon-containing polymer was calculated by GPC measurement (HLC-8320GPC manufactured by Tosoh Corporation) and was 5,900.

[0174] [Synthesis of composite materials]

[0175] 2.5 g of silicon-containing polymer was dissolved in 5 mL of toluene to obtain a first solution. Next, 2 g of ZIF-8 particles were added to 20 mL of toluene, and the particles were dispersed using an ultrasonic cleaner to obtain a second solution. The first solution prepared above was added while stirring the second solution with a magnetic stirrer, and stirred at room temperature for 12 hours. Then, a powder was obtained by filtration. Toluene was added to the obtained powder, and after ultrasonic dispersion, the supernatant was removed by centrifugation. The above-mentioned cleaning operation was repeated 3 times and then dried in the atmosphere. Thus, the composite material particles of Example 1 were obtained.

[0176] [Confirmation of bonding of silicon-containing polymer]

[0177] The fact that the silicon-containing polymer was bonded to the surface of ZIF-8 in the composite material of Example 1 was confirmed by infrared absorption spectrum and O1sXPS spectrum of the composite material. The infrared absorption spectrum was obtained by diffuse reflectance method of Fourier transform infrared spectroscopy (FT-IR).

[0178] exist Figure 8 . The infrared absorption spectrum of the composite material of Example 1 and the infrared absorption spectrum of ZIF-8 are shown in FIG. Figure 8 The horizontal axis represents the wave number (cm -1 ), the vertical axis represents transmittance (%). It should be noted that Figure 8 This is a graph used to compare the trends of two infrared absorption spectra, so the scale of the vertical axis is omitted. Figure 8 As shown, in the composite material of Example 1, a peak P derived from the angular vibration of the vinyl group was observed, thus confirming the presence of a silicon-containing polymer on the surface of ZIF-8.

[0179] exist Fig. 9 The O1s XPS spectrum of the composite material of Example 1 is shown in FIG. Fig.10 The O1s XPS spectrum of ZIF-8 is shown in Fig. 9 and Fig.10 In the figure, the horizontal axis represents the binding energy (eV) and the vertical axis represents the intensity in arbitrary units. Fig. 9 As shown, Si-O-Zn bonds and Si-O-Si bonds were confirmed by peak separation of the O1sXPS spectrum of the composite material of Example 1. These results confirmed that in the composite material of Example 1, the silicon-containing polymer was immobilized on the surface of ZIF-8 via bonding containing Zn-O-Si bonds.

[0180] [Production of films including composite materials]

[0181] The film of Example 1 containing 40% by volume of the composite material particles of Example 1 was prepared by the following method. It should be noted that the density of the composite material particles was set to 0.921 g / cm3 The density of all other components is set to 1g / cm 3 . First, 0.7950 g of reactive low molecular weight (molecular weight 2400) polyphenylene ether as the main component of the resin, 0.0900 g of allyl cyanurate derivative (manufactured by Shikoku Chemical Co., Ltd., product name: L-DAIC) as a crosslinking aid, 0.0150 g of dicumyl peroxide as a polymerization initiator, and 0.5526 g of the composite material particles of Example 1 were added to 5 mL of toluene in order to obtain a mixture. After dispersing the mixture for 3 minutes using an ultrasonic cleaner, a suspension was obtained by stirring it for 30 minutes using a magnetic stirrer. The suspension was heated at 90°C for 1 hour, and then repeatedly vacuumed at 110°C for 3 minutes. Thus, a paste-like solid from which the solvent was removed was obtained. The paste-like solid was pressed at 150°C and 10 MPa for 5 minutes, and then pressed at 190°C and 10 MPa for 5 minutes to solidify it. Then, the membrane of Example 1 was obtained by vacuuming at 200°C for 12 hours. The thickness of the film of Example 1 was 0.273 mm. The thickness of the film was measured at 5 arbitrary points on the film and was obtained as the average value of the measured values.

[0182] <<Comparative Example 1>>

[0183] As MOF, ZIF-8 particles (manufactured by Aldrich, product name: Basolite Z1200) used in Example 1 were used. In Comparative Example 1, polydopamine was used instead of the silicon-containing polymer to synthesize the composite material. Dopamine has attracted attention in recent years as a natural adhesive that strongly bonds to the surface of inorganic fillers. In 100 mL of deionized water, 4.2 g of trishydroxymethylaminomethane was dissolved, and then hydrochloric acid was added to obtain a Tris buffer adjusted to pH 7. Next, 3 g of ZIF-8 particles were added to the Tris buffer, and 2.25 g of dopamine hydrochloride was added while stirring with a magnetic stirrer, and stirred at 80°C for 20 hours. Then, a powder was obtained by filtration. Deionized water was added to the obtained powder, and after ultrasonic dispersion, the supernatant was removed by centrifugation. After the above-mentioned washing operation was repeated 3 times, it was dried in the air to obtain the composite material particles of Comparative Example 1. Since the color of the powder changed from white to gray, which is unique to the dopamine layer, it was confirmed that the dopamine layer modified the surface of the ZIF-8 powder.

[0184] <<Comparative Example 2>>

[0185] As MOF, ZIF-8 particles (manufactured by Aldrich, product name: Basolite Z1200) used in Example 1 were used. In Comparative Example 2, 3-methacryloxypropyl trimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBM-503) was used instead of the silicon-containing polymer to synthesize the composite material. 3-methacryloxypropyl trimethoxysilane is one of the conventional silane coupling agents formed from silicon-containing low molecular weight compounds. The surface modification was performed in the same manner as in Example 1, except that the silicon-containing polymer was changed to 3-methacryloxypropyl trimethoxysilane.

[0186] A film of Comparative Example 2 was produced in the same manner as in Example 1, except that the composite material particles of Comparative Example 2 were used. The thickness of the film of Comparative Example 2 was 0.268 mm.

[0187] Comparative Example 3

[0188] As the particles of Comparative Example 3, the ZIF-8 particles (manufactured by Aldrich, product name: Basolite Z1200) used in Example 1 were used as they were.

[0189] A film of Comparative Example 3 was produced in the same manner as in Example 1, except that the ZIF-8 particles of Comparative Example 3 were used as the composite material particles. The thickness of the film of Comparative Example 3 was 0.260 mm.

[0190] The dielectric properties and chemical stability of each of the particles obtained in Example 1 and Comparative Examples 1 to 3 were evaluated before and after surface modification according to the methods described below.

[0191] [Evaluation of pore volume of particles before and after surface modification]

[0192] The pore volume of ZIF-8 particles at a relative pressure of 0.99 before and after surface modification was measured by nitrogen adsorption at 77 K. As a nitrogen adsorption measuring device, BELSORP MINI X manufactured by Microchip Bayer was used. During the measurement, the particles were pretreated under vacuum (below 10 Pa) at 200°C for 1 hour. The results are shown in Table 1.

[0193] [Evaluation of Dielectric Properties of Particles Before and After Surface Modification]

[0194] The relative dielectric constant and dielectric loss tangent of ZIF-8 particles before and after surface modification were measured by cavity resonance method at a frequency of 1 GHz. As a cavity resonator, MS46122B manufactured by AET was used. During the measurement, the particles were pretreated under vacuum (below 10 Pa), 200°C, and 1 hour. Then, the measurement was carried out in the atmosphere. The filling rate of the sample tube was calculated from the true density of ZIF-8, and the relative dielectric constant and dielectric loss tangent of the particles were calculated. The relative dielectric constant and relative dielectric loss tangent of the particles were calculated by converting the measured values ​​with the filling rate of the sample tube. The filling rate of the sample tube is determined by the mass of the particles, the bulk volume occupied by the particles in the sample tube, and the true density of each particle. As the true density of ZIF-8, the density calculated from the crystal structure (0.921 g / cm 3 ). The true density of the surface-modified particles is determined by the following formulas (X1) and (Y1). The porosity of ZIF-8 is 50%. The results are shown in Table 1. If the relative dielectric constant after surface modification is less than 2.00 and the dielectric loss tangent is less than 0.003, it is judged that the dielectric properties are not deteriorated by surface modification.

[0195] True density of surface-modified particles = (density calculated from the crystal structure of ZIF-8) ÷ ((void ratio of ZIF-8 × 0.01) × (void maintenance ratio) × 0.01) Formula (X1)

[0196] Void maintenance rate = (pore volume of particles after surface modification) ÷ (pore volume of particles before surface modification) Formula (Y1)

[0197] [Evaluation of chemical stability of films before and after etching]

[0198] The relative dielectric constant of the film containing composite material particles before and after etching was measured by the cavity resonance method at a frequency of 40 GHz. As a cavity resonator, MS46122B manufactured by AET was used. The results are shown in Table 1. If the absolute value of the change in the relative dielectric constant before and after etching is less than 0.02, when the film is used as an insulating layer of a wiring board, it is judged to have sufficient chemical stability to the extent that no design obstacles are caused. It should be noted that less than 0.02 is also within the error range of the measuring device (±0.02). The etching process was carried out under the following conditions. As an etching solution, a cupric chloride solution (HCl concentration of 2.5 mol / liter: containing CuCl2, H2O2, H2O) generally used in the patterning of copper plates was used. In the etching solution, a film cut into 4 cm×4 cm was immersed at room temperature for 80 hours. Then, the film was washed with water several times and vacuumed at 40°C for 30 minutes. Thus, a film after etching was obtained.

[0199] Table 1

[0200]

[0201] <<Investigation>

[0202] As shown in Table 1, in Example 1, no deterioration in relative dielectric constant and dielectric loss tangent after surface modification was observed, showing excellent dielectric properties.

[0203] As shown in Table 1, in Example 1, there was almost no change in the relative dielectric constant before and after the etching treatment, showing excellent chemical stability. This is believed to be because in Example 1, the structure of ZIF-8 was almost unchanged by the etching treatment.

[0204] On the other hand, in Comparative Example 1, by surface modification, relative dielectric constant and dielectric loss tangent rise, and dielectric properties deteriorate. It is believed that this is because, when surface modification, inside the void of ZIF-8, polymerization reaction is carried out, and occlusion of void occurs; and hydroxyl (-OH) existing in a large number on dopamine skeleton is exposed on the surface. In Comparative Example 2, although the deterioration of dielectric properties caused by surface modification is slightly relaxed compared with Comparative Example 1, similarly to Comparative Example 3 without surface modification layer, by etching treatment, relative dielectric constant has changed. It is believed that this is because, in Comparative Example 2, by etching treatment, the structure of ZIF-8 collapses, and particles are dissolved in etching solution, and void increases.

[0205] <<Example 2>>

[0206] [Synthesis of Metal-Organic Frameworks (MOFs)]

[0207] As MOF, UiO-67 was used. UiO-67 particles were synthesized by the same synthesis method as that of UiO-67 of sample C-3BA described in Non-Patent Document 8. The fact that the synthesized particles had the structure of UiO-67 was confirmed by powder X-ray diffraction measurement. As a powder X-ray diffraction measurement apparatus, RINT2000 manufactured by Rigaku Corporation was used. As an X-ray source in powder X-ray diffraction, Cu-Kα rays were used. exist Fig.11 An example of an X-ray diffraction pattern of particles synthesized in Example 2 and an X-ray diffraction simulation pattern of UiO-67 predicted from the crystal structure are shown side by side. Fig.11 In the figure, the horizontal axis represents the diffraction angle (2θ) and the vertical axis represents the X-ray intensity. Fig.11This is a diagram for comparing the trends of two X-ray diffraction patterns, so the scale of the vertical axis is omitted. Since the trends of the two X-ray diffraction patterns are similar, it is determined that the crystal structure of the particles synthesized in Example 2 is UiO-67.

[0208] [Silicon-containing polymer]

[0209] As the silicon-containing polymer, the silicon-containing polymer synthesized in Example 1 was used.

[0210] [Synthesis of composite materials]

[0211] Dissolve 1 g of a silicon-containing polymer in 5 mL of toluene to obtain a first solution. Next, add 3 g of UiO-67 particles to 30 mL of toluene, and use an ultrasonic cleaner to disperse the particles to obtain a second solution. While stirring the second solution with a magnetic stirrer, add the first solution prepared above, and stir at room temperature for 12 hours. Then, obtain a powder by filtration. Add toluene to the obtained powder, perform ultrasonic dispersion, and then remove the supernatant by centrifugation. Repeat the above-mentioned cleaning operation 3 times and dry in the air. Thus, the composite material particles of Example 2 are obtained.

[0212] [Confirmation of bonding of silicon-containing polymer]

[0213] Since it was confirmed that the silicon-containing polymer was bonded to the surface of MOF (ZIF-8) in the composite material of Example 1, it is presumed that the silicon-containing polymer in the composite material of Example 2 was also bonded to the surface of MOF (UiO-67) in the same bonding manner.

[0214] <<Comparative Example 4>>

[0215] As MOF, UiO-67 synthesized in Example 2 was used. In Comparative Example 4, polydopamine was used instead of the silicon-containing polymer to synthesize a composite material. Dopamine has attracted attention in recent years as a natural adhesive that strongly bonds to the surface of an inorganic filler. It is known that dopamine forms a polydopamine film by self-oxidative polymerization on the surface of MOF. 4.2 g of trishydroxymethylaminomethane was dissolved in 100 mL of deionized water, and then hydrochloric acid was added to obtain a Tris buffer adjusted to pH = 7. Next, 3 g of UiO-67 particles were added to the Tris buffer, and 2.25 g of dopamine hydrochloride was added while stirring with a magnetic stirrer, and stirred at 80°C for 20 hours. Then, a powder was obtained by filtration. Deionized water was added to the obtained powder, and after ultrasonic dispersion, the supernatant was removed by centrifugation. After the above-mentioned washing operation was repeated 3 times, it was dried in the air to obtain the composite material particles of Comparative Example 1. Since the color of the powder changed from white to gray, which is unique to the dopamine layer, it was confirmed that the dopamine layer modified the surface of the UiO-67 powder.

[0216] <<Comparative Example 5>>

[0217] As MOF, UiO-67 synthesized in Example 1 was used. In Comparative Example 5, 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBM-503) was used instead of the silicon-containing polymer to synthesize the composite material. 3-methacryloxypropyltrimethoxysilane is one of the conventional silane coupling agents formed from silicon-containing low molecular weight compounds. The surface modification was performed in the same manner as in Example 2 except that the silicon-containing polymer was changed to 3-methacryloxypropyltrimethoxysilane.

[0218] 《Comparative Example 6》

[0219] As the particles of Comparative Example 6, UiO-67 synthesized in Example 2 was used directly.

[0220] The dielectric properties and chemical stability of each of the particles obtained in Example 2 and Comparative Examples 4 to 6 were evaluated before and after surface modification according to the methods described below.

[0221] [Evaluation of Dielectric Properties of Particles Before and After Surface Modification]

[0222] The dielectric properties of the UiO-67 particles before and after surface modification were evaluated for the Examples and Comparative Examples using the following three methods.

[0223] [Evaluation of pore volume of particles before and after surface modification]

[0224] The pore volume of the UiO-67 particles before and after surface modification at a relative pressure of 0.99 was measured by nitrogen adsorption measurement at 77K. As a nitrogen adsorption measurement device, BELSORP MINI X manufactured by Microchip Bayer was used. During the measurement, the particles were pretreated under vacuum (below 10Pa), 150°C, and 5 hours. The results are shown in Table 2.

[0225] [Evaluation of Dielectric Properties of Particles Before and After Surface Modification]

[0226] The relative dielectric constant and dielectric loss tangent of UiO-67 particles before and after surface modification were measured by the cavity resonance method at a frequency of 1 GHz. Considering the possibility that the relative dielectric constant and dielectric loss tangent values ​​may be affected by the absorption of moisture in the atmosphere by UiO-67 particles, the relative dielectric constant and dielectric loss tangent were measured in powder form under N2 atmosphere. As a cavity resonator, MS46122B manufactured by AET was used. During the measurement, the particles were pretreated under vacuum (below 10 Pa), 150°C, and 5 hours. Then, the particles were filled into a sample tube under N2 atmosphere without being exposed to the atmosphere, and the measurement was carried out. The filling rate of the sample tube was calculated from the true density of UiO-67, and the relative dielectric constant and dielectric loss tangent of the particles were calculated. The relative dielectric constant and relative dielectric loss tangent of the particles were calculated by converting the measured values ​​with the filling rate of the sample tube. The filling rate of the sample tube is determined by the mass of the particles, the bulk volume occupied by the particles in the sample tube, and the true density of each particle. As the true density of UiO-67, the density calculated from the crystal structure (0.708 g / cm 3 ). The true density of the surface-modified particles is determined by the following formulas (X2) and (Y1). The porosity of UiO-67 is 68%. The results are shown in Table 2. If the relative dielectric constant after surface modification is less than 2.00 and the dielectric loss tangent is less than 0.002, it is judged that the dielectric properties are not deteriorated by surface modification.

[0227] True density of surface-modified particles = (density calculated from the crystal structure of UiO-67) ÷ ((void ratio of UiO-67 × 0.01) × (void maintenance ratio) × 0.01) Formula (X2)

[0228] Void maintenance rate = (pore volume of particles after surface modification) ÷ (pore volume of particles before surface modification) Formula (Y1)

[0229] [Evaluation of Chemical Stability of Particles after Etching]

[0230] The chemical stability of the composite material particles after etching was evaluated for Example 2 and Comparative Examples 4 to 6 using the following three methods.

[0231] [Evaluation of pore volume of particles after etching]

[0232] The pore volume of the composite material particles after etching was measured by the nitrogen adsorption measurement at 77K described above. The results are shown in Table 1. The etching process was carried out under the following conditions. As an etching solution, a cupric chloride solution (HCl concentration of 2.5M: containing CuCl2, H2O2, H2O) generally used in the patterning of copper plates was used. In 5mL of the etching solution, 1g of particles were immersed for 1 minute and stirred. Then, the particles were washed with water and filtered to obtain the particles after etching.

[0233] [Evaluation of Dielectric Properties of Particles After Etching]

[0234] Adopt the cavity resonance method under the frequency of 1GHz mentioned above, measure the relative dielectric constant and dielectric loss tangent of the composite material particles after etching treatment.The relative dielectric constant and dielectric loss tangent of particles are calculated by converting the measured value with the filling rate of sample tube.The filling rate of sample tube is determined by the mass of particles, the accumulated volume occupied by particles in the sample tube, and the true density of each particle.The true density of particles after etching treatment is determined by following formula (X3) and (Y2).The results are shown in Table 2.If the relative dielectric constant after etching treatment is less than 2.00 and the dielectric loss tangent is less than 0.002, it is judged to maintain a low relative dielectric constant of the degree of low dielectric filler applicable as an insulating layer.

[0235] True density of particles after etching = (true density of particles after surface modification) ÷ ((void ratio of UiO-67 × 0.01) × (void maintenance ratio) × 0.01) Formula (X3)

[0236] Void maintenance rate = (pore volume of particles after surface modification) ÷ (pore volume of particles after etching) Formula (Y2)

[0237] The etching process was carried out under the following conditions. As an etching solution, a cupric chloride solution (HCl concentration of 2.5 mol / L: containing CuCl2, H2O2, H2O) was used. 1 g of the particles were immersed in 5 mL of the etching solution for 1 minute and stirred. Then, the particles were washed with water and filtered to obtain the etched particles.

[0238] Table 2

[0239]

[0240] Investigation

[0241] As shown in Table 2, in Example 2, many voids were maintained, and increases in the relative dielectric constant and dielectric loss tangent after surface modification were suppressed.

[0242] As shown in Table 2, in Example 2, even after the etching process, many voids were maintained, and increases in the relative dielectric constant and the dielectric loss tangent were suppressed. That is, the composite material of Example 2 had improved chemical stability.

[0243] On the other hand, in Comparative Example 4, by surface modification, relative dielectric constant and dielectric loss tangent rise. It is believed that this is because, when surface modification, inside the void of UiO-67, polymerization reaction is carried out, and occlusion of the void occurs; and the hydroxyl (-OH) present in large quantities on the dopamine skeleton is exposed on the surface. In Comparative Example 5, although the relative dielectric constant and dielectric loss tangent caused by surface modification are suppressed compared with Comparative Example 4, similarly to Comparative Example 6 without a surface modification layer, by etching, relative dielectric constant and dielectric loss tangent can be greatly increased. It is believed that the reason is that in Comparative Example 5, by etching, the collapse of the three-dimensional porous structure of UiO-67 is promoted.

[0244] As mentioned above, with regard to the composite material of embodiment 1 and embodiment 2, the rise of relative dielectric constant and dielectric loss tangent is suppressed, and chemical stability improves. Therefore, it is estimated that by using such composite material as filler, resin combination has low relative dielectric constant and dielectric loss tangent, and the deterioration of the three-dimensional porous structure of MOF caused by etching can be suppressed. As a result, it is possible to provide a product that can be installed as the insulating layer of wiring board.

[0245] It should be noted that, in Example 1, as MOF, ZIF-8 was used, but it is speculated that even when ZIF-4, ZIF-7, ZIF-12, ZIF-67, ZIF-90 or ZIF-412 are used instead of ZIF-8, the rise of relative dielectric constant and dielectric loss tangent can be suppressed in the same manner, and chemical stability improves. In addition, in Example 2, as MOF, UiO-67 was used, but it is speculated that even when Zr-MOF such as UiO-66, UiO-68, NU-1000, NU-1103, MOF-808, PCN-224, DUT-52, BUT-30 or MIL-140 are used instead of UiO-67, the rise of relative dielectric constant and dielectric loss tangent can be suppressed in the same manner, and chemical stability improves. This is because the composite material of the present disclosure suppresses increases in relative dielectric constant and dielectric loss tangent and achieves improved chemical stability by including MOF and silicon-containing polymer.

[0246] In order to express the present disclosure, the present disclosure is appropriately and fully described above through the embodiments, but it should be recognized that those skilled in the art can easily change and / or improve the above embodiments. Therefore, as long as the changes or improvements implemented by those skilled in the art do not deviate from the level of the scope of rights of the claims recorded in the claims, the changes or improvements should be interpreted as being included in the scope of rights of the claims.

[0247] Industrial Applicability

[0248] The composite material disclosed herein can realize a filler having excellent dielectric properties and chemical stability, and is therefore suitable for use in wiring boards of electronic devices used in large-capacity communications and the like.

[0249] Description of Reference Numerals

[0250] 1 Metal-organic structures

[0251] 2 Silicone-containing polymers

[0252] 10 Composite Materials

[0253] 20. Resin composition

[0254] 22 Filling

[0255] 24 Curing resin

[0256] 30 Membrane with resin

[0257] 32 resin layer

[0258] 34 Support membrane

[0259] 40 Metal foil with resin

[0260] 42 Resin layer

[0261] 44 metal foil

[0262] 50 Metal-clad laminate

[0263] 52 Insulation layer

[0264] 54 metal foil

[0265] 60 Wiring Board

[0266] 62 Insulation layer

[0267] 64 Wiring.

Claims

1. A composite material comprising: a metal organic structure, and a silicon-containing polymer, wherein the silicon-containing polymer comprises a main chain comprising at least one selected from a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit, and a fluorine-containing olefin unit.

2. The composite material according to claim 1, wherein The silicon-containing polymer is attached to the surface of the metal-organic structure.

3. The composite material according to claim 1, wherein The metal-organic structure comprises metal oxide clusters.

4. The composite material according to claim 3, wherein The metal oxide clusters include Zr oxide clusters.

5. The composite material according to claim 1, wherein The silicon-containing polymer includes a first side chain including a silicon atom and an oxygen atom, and is bonded to the metal-organic structure via the silicon atom and the oxygen atom.

6. The composite material according to claim 1, wherein The silicon-containing polymer comprises -SiR 3-n (OX) n The functional group represented by n is an integer from 1 to 3, X represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, a portion bonded to the metal organic structure, or a portion bonded to a silicon atom other than a silicon atom of the functional group, at least one of X is a portion bonded to the metal organic structure, and R represents a hydrocarbon group having 1 to 10 carbon atoms.

7. The composite material according to claim 1, wherein The silicon-containing polymer includes a second side chain including at least one selected from a carbon-carbon double bond and a carbon-carbon triple bond.

8. The composite material according to claim 7, wherein The second side chain is formed only of a chain structure.

9. The composite material according to claim 1, wherein The main chain comprises the butadiene units.

10. The composite material according to claim 9, wherein The main chain includes a copolymer including the styrene unit and the butadiene unit.

11. The composite material according to claim 6, wherein The silicon-containing polymer is represented by the following formula (1) comprising a plurality of repeating units, [Chemical formula number 1] In the above formula (1), a and d represent numbers greater than 0, b and c represent numbers greater than 0, and R 1 To R 5 independently represent a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom or -CH3, The order of the plurality of repeating units is arbitrary.

12. The composite material according to claim 11, wherein In the above formula (1), 0.15≤c / (b+c+d) is satisfied.

13. The composite material according to claim 1, wherein The metal organic structure comprises UiO-67. A filler comprising the composite material according to claim 1. 15 . A resin composition comprising the filler according to claim 14 . 16 . A prepreg comprising the resin composition according to claim 15 or a semi-cured product of the resin composition. 17 . A film with a resin, comprising: a resin layer comprising the resin composition according to claim 15 or a semi-cured product of the resin composition; and a supporting film. 18 . A metal foil with resin, comprising: a resin layer comprising the resin composition according to claim 15 or a semi-cured product of the resin composition; and a metal foil. 19 . A metal-clad laminate comprising: an insulating layer comprising a cured product of the resin composition according to claim 15 or a cured product of the prepreg according to claim 16; and a metal foil. 20 . A wiring board comprising: an insulating layer comprising a cured product of the resin composition according to claim 15 or a cured product of the prepreg according to claim 16 ; and wiring.

21. A method for producing a composite material, comprising the step of attaching a silicon-containing polymer to a metal organic structure, wherein the silicon-containing polymer comprises a main chain comprising at least one selected from a styrene unit, a butadiene unit, an ethylene unit, a cycloolefin unit and a fluorine-containing olefin unit.

22. The method for producing a composite material according to claim 21, wherein: The metal-organic structure comprises metal oxide clusters.

23. The method for producing a composite material according to claim 21, wherein: The number average molecular weight of the silicon-containing polymer is greater than 1200.

Citation Information

Patent Citations

  • Organosilicon compound, and compounding agent for rubber and rubber composition using the same

    JP2016191040A

  • Resin composition for forming insulation film

    JP2018080327A